A new approach based a genetic algorithm for the selective travelling salesman problem - Laarabi, Bochar; Bouchaib, Radi (Colloquium in Information Science and Technology (Print), 2016)
In this paper presents a new approach based a genetic algorithm to solve selective travelling salesman problem, which is concerned with finding a path between a given set of control points, among which a start and an end point are the same, and to maximize the total gain collected subject to a prescribed cost constraint. This approach assured by creation of a population under the criterion ratio between the gain and cost. The results of the application of this approach give us the best of the objective function and the number of iterations for algorithm is reduced.